1994
DOI: 10.1007/bf00241097
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin-induced contraction of guinea pig lung in vitro

Abstract: We have investigated the contractile effect of bradykinin (BK) in guinea pig lung in vitro. BK induces a dose-related contraction of lung parenchymal strips which is increased significantly in the presence of 10(-5) M captopril (an angiotensin converting enzyme inhibitor) or 10(-5) M DL-thiorphan (a neutral endopeptidase inhibitor). The kininase I inhibitor, DL-2-mercaptomethyl-3-guanidino-ethylthiopropionic acid (MGTPA), has no effect on the BK-induced contraction. BK is more potent in contracting parenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We found that HHcy significantly enhanced BK-induced constrictions of arterioles ( Figure 2A), which were likely due to an increased synthesis of PGH 2 / TxA 2 , as both indomethacin and SQ 29,548 substantially inhibited the responses, thereby eliminating the difference between HHcy and control arterioles (Figures 2B and 2C). Furthermore, the findings that the specific TxA 2 synthase inhibitor furegrelate 30 inhibited BK-induced constrictions and also eliminated the difference between responses in control and HHcy arterioles ( Figure 2D) indicate that TxA 2 is the primary constrictor prostaglandin synthesized to BK in arterioles of HHcy rats.…”
Section: Discussionmentioning
confidence: 88%
“…We found that HHcy significantly enhanced BK-induced constrictions of arterioles ( Figure 2A), which were likely due to an increased synthesis of PGH 2 / TxA 2 , as both indomethacin and SQ 29,548 substantially inhibited the responses, thereby eliminating the difference between HHcy and control arterioles (Figures 2B and 2C). Furthermore, the findings that the specific TxA 2 synthase inhibitor furegrelate 30 inhibited BK-induced constrictions and also eliminated the difference between responses in control and HHcy arterioles ( Figure 2D) indicate that TxA 2 is the primary constrictor prostaglandin synthesized to BK in arterioles of HHcy rats.…”
Section: Discussionmentioning
confidence: 88%
“…Inconsistency between in vivo (Ricciardolo et al , 1994) and our in vitro results may reflect differences in de novo synthesis of kinins, although generation of kinins in airway preparations has been demonstrated (Farmer et al , 1994). It has also been shown in both guinea‐pig (Arakawa et al , 1992; Lach et al , 1994) and human (Molimard et al , 1994) airways that bradykinin exerts part of its effect through a pathway that is sensitive to indomethacin (a cyclo‐oxygenase inhibitor). Prostanoid synthesis may originate from the airway epithelium (Lindström et al , 1992), which could in part explain the divergent results obtained with our epithelium‐denuded preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Although a NO-pathway has been described to be partly involved in bradykinin-induced tracheal relaxation (Schlemper and Calixto 1994) and to modulate bronchoconstriction in response to bradykinin (Belvisi et al 1992), the bradykinin-induced lung contraction (Lach et al 1994) appears to be unaffected by L-NAME. In addition, L-NAME did not significantly modify lung responsiveness to carbachol.…”
Section: Discussionmentioning
confidence: 99%